Diseases of the Aorta and Kidney Disease: conclusions from a Kidney Disease: Improving Global Outcomes (KDIGO) Controversies Conference . Issue 12 (1st September 2021) - Sarafidis, Pantelis; Martens, Sven; Saratzis, Athanasios; Kadian-Dodov, Daniella; Murray, Patrick T; Shanahan, Catherine M; Hamdan, Allen D; Engelman, Daniel T; Teichgräber, Ulf; Herzog, Charles A; Cheung, Michael; Jadoul, Michel; et al.
Abstract: Chronic kidney disease (CKD) is an independent risk factor for the development of abdominal aortic aneurysm (AAA), as well as for cardiovascular and renal events and all-cause mortality following surgery for AAA or thoracic aortic dissection. In addition, the incidence of acute kidney injury (AKI) after any aortic surgery is particularly high, and this AKI per se is independently associated with future cardiovascular events and mortality. On the other hand, both development of AKI after surgery and the long-term evolution of kidney function differ significantly depending on the type of AAA intervention (open surgery vs. the various subtypes of endovascular repair). Current knowledge regarding AAA in the general population may not be always applicable to CKD patients, as they have a high prevalence of co-morbid conditions and an elevated risk for periprocedural complications. This summary of a Kidney Disease: Improving Global Outcomes Controversies Conference group discussion reviews the epidemiology, pathophysiology, diagnosis, and treatment of Diseases of the Aorta in CKD and identifies knowledge gaps, areas of controversy, and priorities for future research.